Shakespeare as a Way of Life : Skeptical Practice and the Politics of Weakness - Kuzner, James (Book collections on Project MUSE., 2016)
Shakespeare is worth reading because his works help us to make epistemological weakness into a way of life. Kuzner shows how Shakespeare's works offer a means for coming to terms with basic uncertainties about freedom, the world's abundance, and the demands of love and social life.